2021
DOI: 10.1021/acs.est.0c06685
|View full text |Cite
|
Sign up to set email alerts
|

Target, Nontarget, and Suspect Screening and Temporal Trends of Per- and Polyfluoroalkyl Substances in Marine Mammals from the South China Sea

Abstract: Per- and polyfluoroalkyl substances (PFASs) have been manufactured and widely used for over 60 years. Currently, there are thousands of marketed PFASs, but only dozens of them are routinely monitored. This work involved target, nontarget, and suspect screening of PFASs in the liver of Indo-Pacific humpback dolphin (Sousa chinensis) and finless porpoise (Neophocaena phocaenoides), two resident marine mammals in the South China Sea, stranded between 2012 and 2018. Among the 21 target PFASs, perfluorooctane sulfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
70
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 66 publications
3
70
0
Order By: Relevance
“…In 2006, PFOS was considered a priority substance under the EU Water Framework Directive (WFD), which restricts the production and use of PFOS throughout the European Union [ 28 ]. As a globally present environmental pollutant, PFOS was recognized as a persistent organic pollutant (POP) in 2009 and was listed in the Stockholm Convention to call for global production restrictions [ 29 ]. The Stockholm Convention has been ratified by 179 countries and measures have been introduced to restrict the production and use of PFOS [ 30 , 31 ], and PFOS has been phased out or banned in Canada [ 32 ], the United States [ 33 ], and the European Union [ 34 ].…”
Section: Profile Of Pfosmentioning
confidence: 99%
“…In 2006, PFOS was considered a priority substance under the EU Water Framework Directive (WFD), which restricts the production and use of PFOS throughout the European Union [ 28 ]. As a globally present environmental pollutant, PFOS was recognized as a persistent organic pollutant (POP) in 2009 and was listed in the Stockholm Convention to call for global production restrictions [ 29 ]. The Stockholm Convention has been ratified by 179 countries and measures have been introduced to restrict the production and use of PFOS [ 30 , 31 ], and PFOS has been phased out or banned in Canada [ 32 ], the United States [ 33 ], and the European Union [ 34 ].…”
Section: Profile Of Pfosmentioning
confidence: 99%
“…Recent studies have identied EOF and different classes of emerging PFAS in various environmental media. [23][24][25][26][27][28][29] These techniques, however, were mostly applied to wastewater or biota samples. Studies focusing on drinking water are limited.…”
Section: Introductionmentioning
confidence: 99%
“…PFECHS presents a lower bioaccumulation factor (BAF) than PFOS in Carassius carassius (Wang et al, 2016) while the contrary is observed for 6:2 Cl-PFESA in zebrafish (Tu et al, 2019). The latter was reported in Greenland marine mammals (Gebbink et al, 2016), fish and marine organisms from China (Shi et al, 2015;Liu et al, 2017;Wang et al, 2021). HFPO-DA and ADONA have never been measured in aquatic biota and exhibit low bioaccumulation potential (Munoz et al, 2019).…”
Section: Introductionmentioning
confidence: 96%